2021
DOI: 10.3390/polym13111716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives during Interfacial Polymerization Reaction for Fabrication of Organic Solvent Nanofiltration (OSN) Membranes

Abstract: Thin film composite (TFC) membranes is the dominant type of desalination in the field of membrane technology. Most of the TFC membranes are fabricated via interfacial polymerization (IP) technique. The ingenious chemistry of reacting acyl chlorides with diamines at the interface between two immiscible phases was first suggested by Cadotte back in the 1980s, and is still the main chemistry employed now. Researchers have made incremental improvements by incorporating various organic and inorganic additives. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…used two different surfactants, including tributyl phosphate (TBP) and SDS. A synergistic effect could be obtained to enhance both the membrane permeate flux and rejection in organic solvents [149] . They indicated that TBP could enhance the solubility of the diamine monomer, and SDS surfactant could efficiently stabilize the IP reaction interface.…”
Section: Recent Advances In Different Parts Of Tfc and Tfn Osn Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…used two different surfactants, including tributyl phosphate (TBP) and SDS. A synergistic effect could be obtained to enhance both the membrane permeate flux and rejection in organic solvents [149] . They indicated that TBP could enhance the solubility of the diamine monomer, and SDS surfactant could efficiently stabilize the IP reaction interface.…”
Section: Recent Advances In Different Parts Of Tfc and Tfn Osn Membranesmentioning
confidence: 99%
“…A synergistic effect could be obtained to enhance both the membrane permeate flux and rejection in organic solvents. [149] They indicated that TBP could enhance the solubility of the diamine monomer, and SDS surfactant could efficiently stabilize the IP reaction interface. However, they reported that the membrane performance was significantly enhanced by the addition of SDS surfactant, as an additive.…”
Section: Surfactantmentioning
confidence: 99%
“…One of the key factors affecting the IP process is the selection of the solvents. For thin-film synthesis, and in particular for thin-film composite membranes, generally water and an organic solvent are used. By varying the organic solvent and adding cosolvents to the aqueous phase, nanofilms with the desired properties can be obtained. The number of studies in which water is substituted by an organic solvent is limited. Wamser et al showed the formation of various polyamide porphyrin films at the interface of dimethylsulfoxide (DMSO)/chloroform and dimethylsulfoxide (DMSO)/ethyl acetate . Ogata et al reported IP in nonaqueous systems to be useful for synthesizing aromatic polyesters and copolyesters .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one of the increasing areas of NF membrane application is in acid wastewater treatment and reclamation processes. , Recently, polyethyleneimine (PEI) and cyanuric chloride (CC) have been used as reactants in preparing acid-stable NF membranes to meet these demands. , Their formation usually results in a tight polyamine network with good separation performance and robust chemical stability, especially in extreme conditions. , More importantly, their (i.e., PEI/CC combination) physicochemical properties and acid stability have been proven to further improve when synthesized during IP with crosslinkers, phase catalysts, surfactants, and green solvents. , However, none of these studies have paid attention to the synergetic relationship between the IP-modified membranes and their performances toward both acid exposure and fouling resistance properties. As wastewater with acid contents may often contain some inorganic impurities that could easily foul the membrane surface while in use, it is therefore imperative to factor in how this problem can be solved, even at the membrane preparation stage in order to fabricate a sustainable and structurally stable NF membranes with good antifouling performance for emerging environmental applications in water and wastewater treatment/recovery.…”
Section: Introductionmentioning
confidence: 99%